The Separation of Free Bran by Using Electricity-Assisted Electrostatic Field System - Sema Nur Kayıran; Ramazan Koç; Mustafa Bayram (Turkish Journal of Agriculture: Food Science and Technology)
In this study, it was to identify a method for separating the free bulgur bran from the fine bulgur during the production of bulgur. This was attempted by creating an electrostatic field using a PVC surface. It was observed that the issue of free bran, which adversely affects the packaged products visually, was effectively solved by this method. In contrast to conventional techniques, an alternative methodology was employed which utilizing a device comprising a folded PVC surface (folded curved channel). The configuration of the experimental apparatus was developed with dimensions of 4, 5 and 6 cm in width, 20, 40 and 60 cm in length, and angles of 30, 35 and 40 degrees, respectively. At the end of the PVC surface, plates were placed to create an electric field. In order to create the electric field, one of the plates was charged with a positive and the other with a negative charge. The distance between the plates was varied according to the width of the tunnel. The expected results were obtained in the layered PVC system. Consequently, a fine bulgur mixture consisting of 5 g of bran per 1000 g of bulgur was introduced into the experimental system at a flow rate of 0.89 g/s. This resulted in a notable reduction in the free bran content, which decreased from 5 g to approximately 2 g.